THE REPRESENTATION OF CULTURAL CONTENT IN GLOBAL ELEMENTARY COURSEBOOK - Stefania Supangat; Flora Debora Floris (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study was to find out the types of cultural content source found in the reading and listening texts presented in Global elementary coursebook (2012) and the similarities and differences of the types of cultural content source found in those texts. The data were analyzed using the theory of types of cultural content source proposed by Matsuda (2012). The findings of this study showed that the reading texts met 54.9% of global culture, 35.3% of target culture, and 9.8% of local culture while the listening texts met 72.5% of global culture, 25% of target culture, and 2.5% of local culture. All in all, as proposed by Matsuda (2012), a good coursebook is the one that has multiple sources of cultural content; and Global elementary coursebook fulfills this criterion as it has three types of cultural content source.